2021
DOI: 10.1021/acsaelm.0c00671
|View full text |Cite
|
Sign up to set email alerts
|

Large Remnant Polarization in a Wake-Up Free Hf0.5Zr0.5O2 Ferroelectric Film through Bulk and Interface Engineering

Abstract: A wake-up free Hf0.5Zr0.5O2 (HZO) ferroelectric film with the highest remnant polarization (Pr) value to-date was achieved through tuning of the ozone pulse duration, the annealing process, and the metal/insulator interface. The ozone dosage during the atomic layer deposition of HZO films appears to be a crucial parameter in suppressing the mechanisms driving the wake-up effect. A tungsten capping electrode with a relatively low thermal expansion coefficient enables the induction of an in-plane tensile strain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(145 citation statements)
references
References 48 publications
7
138
0
Order By: Relevance
“…Finally, W/HZO/W capacitors with different electrode areas were passed through an annealing process in ambient N 2 under two different conditions, i.e., 500 C for 30 s (A1) and 700 C for 5 s (A2), to achieve different t-/o-phase ratios f t o according to the previous studies. [35,42] The elemental composition was evaluated through X-ray photoelectron spectroscopy (XPS). High-resolution transmission electron microscopy (HRTEM) and an X-ray reflectometer (XRR) were used to measure the film thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, W/HZO/W capacitors with different electrode areas were passed through an annealing process in ambient N 2 under two different conditions, i.e., 500 C for 30 s (A1) and 700 C for 5 s (A2), to achieve different t-/o-phase ratios f t o according to the previous studies. [35,42] The elemental composition was evaluated through X-ray photoelectron spectroscopy (XPS). High-resolution transmission electron microscopy (HRTEM) and an X-ray reflectometer (XRR) were used to measure the film thickness.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness of the thin film was approximately 10 nm, and an o-phase crystalline structure was mainly observed. The disappearance of the o-phase structure near the interface is thought to be because of interface instability due to TiN diffusion [ 13 , 27 ]. Figure 3 b shows the EDS-based elemental composition profiles of the same thin film, and it can be observed that some of the Ti and N atoms diffused into the HZO thin film.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, studies on improving the properties of HZO have been actively underway. In particular, research on the effects of crystal structure, oxygen defects inside thin films, grain size, and interface engineering using electrodes on changes in electrical properties has been mainly reported [ 10 , 11 , 12 , 13 , 14 ]. HZO thin films have a variety of crystalline phases such as tetragonal (t-, P4 2 /nmc), monoclinic (m-, P2 1 /c), and orthorhombic (o-, Pca2 1 ) phases, of which the o-phase exhibits ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated ferroelectric polarization of the orthorhombic Pca21 phase of HfO2 is about 50.2 µC/cm 2 , which is consistent with the previous theoretical studies. [10][11][12][13][14] The polarization is directed along the c-axis, as enforced by the symmetry of the crystal, so that the a-and bcomponents of polarization are zero. The 5% Y doping slightly reduces the polarization down to about 49.9 µC/cm 2 , which indicates that Y does not play a decisive intrinsic role in high polarization values observed in our experiments, but rather helps to stabilize the orthorhombic Pca21 phase of hafnia.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…The small crystal grain sizes lead to proliferation of structural defects (low crystallinity) in the form of grain boundaries, which are expected to undermine and obscure ferroelectric properties. 9 Indeed, it has been challenging to elucidate the crystal structure of the ferroelectric o-phase; to date, most of the experimentally observed spontaneous polarization values are significantly lower than the theoretically predicted ones (40-60 µC/cm 2 ) [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%